Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan pada Sub Sektor Perbankan di Indonesia - Agus Musalim; Riana R Dewi; Dimas Ilham Nur Rois (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of profitability and liquidity on firm value in 22 banks listed on the Indonesia Stock Exchange during the period 2018-2023. Profitability is measured by Return on Assets (ROA) and Return on Equity (ROE), while liquidity is measured by Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER). Firm value is proxied by Price to Book Value (PBV). Multiple linear regression analysis is used to test the research hypothesis. The results showed that profitability (ROA and ROE) and liquidity (LDR and DER) have a positive effect on firm value. This study underscores the importance of maintaining healthy profitability and liquidity levels for banks to increase their firm value.